The Burnout Phenomenon: A Résumé After More Than 15,000 Scientific Publications - Hillert, Andreas; Albrecht, Arnd; Voderholzer, Ulrich (Frontiers in Psychiatry, 2020)
The “burnout” phenomenon, supposedly caused by work related stress, is a challenge for academic psychiatry both conceptually and professionally. Since the first description of burnout in 1974 until today, more than 140 definitions have been suggested. Burnout–symptomatology's main characteristic, the experience of exhaustion, is unspecific. Different development–models of burnout were proposed, assumed to depict a quasi-natural process. These could not be confirmed empirically. An expert consensus on the diagnostic criteria and the conceptual location, whether as an independent disorder or as a risk, could not be agreed on. Nevertheless, the phenomenon of burnout in the ICD-11 is considered to be categorized as a work-related disorder. Psychiatric research on the burnout–phenomenon ignores problems of definition resulting from different perspectives: It may meet societal expectations, but does not fulfill scientific criteria, and therefore is not suitable to establish an objective diagnosis and treatment. Parallel detection of ICD/DSM diagnoses from an expert perspective and subjective perturbation models are considered appropriate.